2016
DOI: 10.1016/j.eucr.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Causing Serotonin Syndrome Following Cystocele Repair

Abstract: Methylene blue is an intravenously administered agent that may potentiate serotonin syndrome. The usage of methylene blue to evaluate ureters for injuries and patency during urological surgeries is recognized as common practice. However, there is no mention of serotonin syndrome caused by methylene blue in urological literature or for urological surgery. We report the first urological case in order to raise awareness of the risk for serotonin toxicity with utilizing methylene blue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In spite of its application in several industries, MB is toxic in nature and will adversely affects both humans and animals. The major health issues in humans are headache, vomiting, diarrhea, sore eyes, cyanosis, Heinz body formation, delirium and tissue necrosis [34,45,93]. MB mainly enter into the water bodies through chemical industries, and it remain as persistent pollutant in water.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of its application in several industries, MB is toxic in nature and will adversely affects both humans and animals. The major health issues in humans are headache, vomiting, diarrhea, sore eyes, cyanosis, Heinz body formation, delirium and tissue necrosis [34,45,93]. MB mainly enter into the water bodies through chemical industries, and it remain as persistent pollutant in water.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, it has been reported that depressive or anxiety patients taking serotonergic medications experienced ST, also referred to as serotonin syndrome, after MB administration. The investigators and medical doctors have believed that the toxicity is deeply linked with the synergism of MB and the medications, and that such patients may be more vulnerable to ST (Ng et al, 2008;Ng and Cameron, 2010;Kapadia et al, 2016;Wolvetang et al, 2016).…”
Section: Serotonin Toxicitymentioning
confidence: 99%
“…ST is characterized by the excessive accumulation of serotonin into the body, which, ultimately, leads to neuromuscular hyperexcitability by the excessive serotonergic agonism of the central and peripheral nervous system, whose clinical findings include agitation, tremor, inducible and ocular clonus, diaphoresis, hyperreflexia, hypertonia, and hyperthermia (over 38 • C) (Boyer and Shannon, 2005). A great number of case reports showed that these events occurred predominantly in mental patients who had been taking serotonergic antidepressant medications including fluoxetine [a selective serotonin reuptake inhibitor (SSRI)] (Martindale and Stedeford, 2003;Kapadia et al, 2016), paroxetine, a SSRI (Bach et al, 2004;Mihai et al, 2007;Ng et al, 2008;Shanmugam et al, 2008;Schwiebert et al, 2009;Wolvetang et al, 2016), venlafaxine [a selective serotonin and norepinephrine reuptake inhibitor (SSNRI)] (Majithia and Stearns, 2006), citalopram, a SSRI (Mathew et al, 2006;Pollack et al, 2009), duloxetine, a SSNRI (Rowley et al, 2009), and clomipramine [a serotonin reuptake inhibitor (SRI)] (Khan et al, 2007), and have been commonly interpreted to be attributed to the reaction of MB as a potent monoamine oxidase A (MAO-A) inhibitor (Gillman, 2011;Top et al, 2014). In effect, MAO has a part in the degradation process of a diversity of monoamines such as serotonin, epinephrine, norepinephrine, dopamine, and histamine (Yeung et al, 2019;Floris et al, 2020).…”
Section: Serotonin Toxicitymentioning
confidence: 99%
“…Other possible adverse effects include nausea, sickness, excessive perspiration, mental disorientation, and methemoglobinemia. 46–48 Despite the fact that there are several reports of photocatalytic MB degradation using TiO 2 -based photocatalysts, the majority of the experiments were conducted using UV light irradiation. Nanoscale materials such as FeSe are a potential photocatalyst, due to their strong broadband-light excited photocatalytic activity, non-cytotoxicity, chemical stability, luminous properties, and commercial availability.…”
Section: Introductionmentioning
confidence: 99%